(untitled) (مجلة المنصور, 2023)
The world nowadays is an increasingly interconnected society where the information & communications technologies has witnessed a great improvement in efficiency &customer service that’s why the electronic government try to have a great role in offering services to citizens by the integration of communications technologies in the process of governance to help the citizens to get service 24 hours aday, 7 days in a week. The aim of this research is to clarify the concept, benefits, objectives & the challenges of e-government and all so to present a proposal system design for the implementation of e-government in the public retirement directorate. Finally the research reached a set of conclusions & recommendations.